2010
DOI: 10.1074/jbc.m110.104083
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Meiotic DNA Double Strand Breaks Requires Cyclin-dependent Kinase and Multiple Nucleases

Abstract: Meiotic recombination requires the formation of programmed Spo11-dependent DNA double strand breaks (DSBs). In Saccharomyces cerevisiae, the Sae2 protein and the Mre11-Rad50-Xrs2 complex are necessary to remove the covalently attached Spo11 protein from the DNA ends, which are then resected by so far unknown nucleases. Here, we demonstrate that phosphorylation of Sae2 Ser-267 by cyclin-dependent kinase 1 (Cdk1) is required to initiate meiotic DSB resection by allowing Spo11 removal from DSB ends. This finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 38 publications
(29 reference statements)
2
56
0
1
Order By: Relevance
“…DSB formation and processing are highly coordinated events during meiosis, and the intermediates with Spo11 attached to ends, or products of MRX-Sae2 processing are not observed in wild-type cells (Zakharyevich et al 2010). STR-Dna2 does not contribute to resection in meiosis, except in the absence of the Dmc1 recombinase (Manfrini et al 2010;Zakharyevich et al 2010). Loss of Exo1 nuclease activity does not significantly impair meiotic recombination, indicating that the short ssDNA tails generated by MRX and Sae2 are sufficient for homologous pairing (Zakharyevich et al 2010).…”
Section: Resection Of Meiotic Dsbsmentioning
confidence: 99%
“…DSB formation and processing are highly coordinated events during meiosis, and the intermediates with Spo11 attached to ends, or products of MRX-Sae2 processing are not observed in wild-type cells (Zakharyevich et al 2010). STR-Dna2 does not contribute to resection in meiosis, except in the absence of the Dmc1 recombinase (Manfrini et al 2010;Zakharyevich et al 2010). Loss of Exo1 nuclease activity does not significantly impair meiotic recombination, indicating that the short ssDNA tails generated by MRX and Sae2 are sufficient for homologous pairing (Zakharyevich et al 2010).…”
Section: Resection Of Meiotic Dsbsmentioning
confidence: 99%
“…Given that a number of nucleases are involved in the resection process (Mimitou and Symington 2009;Zakharyevich et al 2010;Garcia et al 2011;Schaetzlein et al 2013), an appealing model is that the MCN ensures appropriate resection rates by activating some nucleases, while (temporarily) inhibiting others (Segurado and Diffley 2008;Manfrini et al 2010;Luo et al 2013;Souquet et al 2013). In S. cerevisiae, resection by BLM Sgs1 /DNA2, in particular, is likely only activated late in meiosis (Manfrini et al 2010;Zakharyevich et al 2010). …”
Section: Control Of Dsb Repair Activation Of Dsb End Processingmentioning
confidence: 99%
“…Resection is initiated by MRE11-dependent endonucleolytic incisions near DSBs, followed by bidirectional resection that requires both MRN and EXO1 (Zakharyevich et al 2010;Garcia et al 2011 and the 9-1-1 complex are also required to restrain hyperresection (Shinohara et al 2003;Gray et al 2013;Clerici et al 2014). Given that a number of nucleases are involved in the resection process (Mimitou and Symington 2009;Zakharyevich et al 2010;Garcia et al 2011;Schaetzlein et al 2013), an appealing model is that the MCN ensures appropriate resection rates by activating some nucleases, while (temporarily) inhibiting others (Segurado and Diffley 2008;Manfrini et al 2010;Luo et al 2013;Souquet et al 2013). In S. cerevisiae, resection by BLM Sgs1 /DNA2, in particular, is likely only activated late in meiosis (Manfrini et al 2010;Zakharyevich et al 2010).…”
Section: Control Of Dsb Repair Activation Of Dsb End Processingmentioning
confidence: 99%
“…Work mostly performed in Saccharomyces cerevisiae and Schizosaccharomyces pombe demonstrated that the SPO11 proteins are subsequently released together with a short DNA oligonucleotide by an endonucleolytic cleavage adjacent to the break site, mediated by the Mre11/Rad50/Xrs2-Nbs1 (MRX/N) complex in conjunction with Sae2/Com1 (Neale et al, 2005;Hartung et al, 2007;Uanschou et al, 2007;Milman et al, 2009). The DNA break sites therefore have, as demonstrated for S. cerevisiae and S. pombe, protruding 39 termini, which are further extended by resection of the 59 termini depending on the activities of the MRX/N complex and Exo1 (Cromie and Smith, 2008;Mimitou and Symington, 2008;Farah et al, 2009;Manfrini et al, 2010;Zakharyevich et al, 2010;Garcia et al, 2011). The extensive single-stranded DNA (ssDNA) overhangs are bound by the heterotrimeric replication protein A (RPA) complex with high affinity, a prerequisite for the loading of the strand-exchange proteins Rad51 and Dmc1 (reviewed in Fanning et al, 2006;Broderick et al, 2010).…”
Section: Introductionmentioning
confidence: 99%